Takotsubo syndrome and respiratory diseases: a systematic review. Issue 2 (24th February 2022) - Li, Pengyang; Wang, Yanxuan; Liang, Jing; Zuo, Xinyu; Li, Qiuyue; Sherif, Akil Adrian; Zhang, Jingyi; Xu, Yidan; Huang, Zirui; Dong, Man; Teng, Catherine; Pan, Su; et al.
Abstract: Takotsubo syndrome (TTS) is a rare cardiovascular condition characterized by reversible ventricular dysfunction and a presentation resembling that of acute myocardial infarction. An increasing number of studies has shown the association of respiratory diseases with TTS. Here, we comprehensively reviewed the literature and examined the available evidence for this association. After searching PubMed, EMBASE, and Cochrane Library databases, two investigators independently reviewed 3117 studies published through May 2021. Of these studies, 99 met the inclusion criteria ( n  = 108 patients). In patients with coexisting respiratory disease and TTS, the most common TTS symptom was dyspnoea (70.48%), followed by chest pain (24.76%) and syncope (2.86%). The most common type of TTS was apical, accounting for 81.13% of cases, followed by the midventricular (8.49%), basal (8.49%), and biventricular (1.89%) types. Among the TTS cases, 39.82% were associated with obstructive lung disease and 38.89% were associated with pneumonia. Coronavirus disease 2019 (COVID-19), which has been increasingly reported in patients with TTS, was identified in 29 of 42 (69.05%) patients with pneumonia. The overall mortality rate for patients admitted for respiratory disease complicated by TTS was 12.50%. Obstructive lung disease and pneumonia are the most frequently identified respiratory triggers of TTS. Medications and invasive procedures utilized in managing respiratory diseases may also contribute to the development of TTS. Furthermore, the diagnosis of TTS triggered by these conditions can be challenging due to its atypical presentation. Future prospective studies are needed to establish appropriate guidelines for managing respiratory disease with concurrent TTS. Graphical Abstract: